People Pleaser Behavior within the Perspective of Sungkan: A Psycho-Anthropological Interpretation - Faiqal Dima Hanif; Rinta Anjani Oktafiani; Dewi Kurnia Rachmawati; Talitha Vania Sasikirana (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
Respect is highly valued in Javanese culture, particularly in social interactions. Children in Javanese culture are taught how to show respect to others, which in Javanese culture consists of three inseparable components, namely sungkan, wedi, and isin. This study identified a case of sungkan behavior in a college student in Yogyakarta, accompanied by a hint of another behavioral concept, namely, people-pleasing. People-pleasing behavior can be viewed from multiple perspectives, one of which is the sungkan culture, a cultural norm rooted in respect, modesty, and avoidance of conflict. This cultural framework provides valuable insight into the dynamics of people-pleasing behavior. This study aims to explore and interpret how people pleaser behave within the context of Javanese culture, specifically examining the extent to which the concept of habitus is internalized in such behavior, using a case study approach. The study explores key themes, including the habitus of people-pleasing behavior, symbolic capital and power within the Javanese family, the individual's attitudes toward family dynamics, awareness from others of people-pleasing behavior, and its psychological and social impacts. This study contributes to the integration of psychology and anthropology by demonstrating that behavior is an expression of symbolic structures in people-pleasing behavior within the concept of sungkan in the Javanese context.